2021
DOI: 10.1177/0091217421989141
|View full text |Cite
|
Sign up to set email alerts
|

The role of identity in chronic pain cognitions and pain-related disability within a clinical chronic pain population

Abstract: Objective Chronic pain has a significant impact on functioning and results in the disruption of one’s assumed life trajectory, potentially altering their self-perceived identity. The present research is designed to determine whether identity-related issues are associated with common chronic pain cognitions and pain-related disability, which may help inform understanding of clinical chronic pain populations. Method Ninety-eight adult chronic pain patients were assessed at a local pain clinic during a regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, at least two studies showed mixed results regarding pain catastrophizing and its role in mutually maintaining chronic pain and PTSD. These results are important because other research shows that pain catastrophizing is associated with death anxiety and self-concept (Reed, Cobos, Nagpal, et al, 2021). Therefore, examining pain catastrophizing within the context of the mutual maintenance model may be helpful.…”
Section: Situational/state Event Processingmentioning
confidence: 83%
See 3 more Smart Citations
“…However, at least two studies showed mixed results regarding pain catastrophizing and its role in mutually maintaining chronic pain and PTSD. These results are important because other research shows that pain catastrophizing is associated with death anxiety and self-concept (Reed, Cobos, Nagpal, et al, 2021). Therefore, examining pain catastrophizing within the context of the mutual maintenance model may be helpful.…”
Section: Situational/state Event Processingmentioning
confidence: 83%
“…Existential anxiety is particularly heightened after experiencing adverse events (Koole et al, 2006). Therefore, it is no surprise that both chronic pain and PTSD are associated with increased existential anxiety, such as loss of self-concept (Dezutter et al, 2015; Fischer et al, 2020; Reed, Cobos, Nagpal, et al, 2021; Vail et al, 2019). However, current models of co-occurring chronic pain and PTSD do not recognize existential anxiety as a component of the comorbidity.…”
Section: Current Models Of Co-occurring Chronic Pain and Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Separately, these disorders are associated with negative changes in social relationships, sense of purpose, identity, and spiritual concerns. [38][39][40][41][42][43][44][45] Core WH services may have a particular impact on issues surrounding personal meaning and purpose, setting personal health goals, and focusing on issues that are typically not medically focused. Thus, holistic approaches to care, either as stand-alone treatments or in adjunct with more conventional treatments, may offer particular advantages and benefits for many patients.…”
Section: Discussionmentioning
confidence: 99%